Інформаційно-методична основа визначення оцінки екологічності складних природно-техногенних об’єктів - Kozulia, T. V.; Bilova, M. O. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2017)
The basic ways are identified to improve the integrated system of safety evaluation of the state of the complex natural and man-made objects according to the identification of destabilizing factors for the purpose of controlling the sustainable development and employing the control measures. The prospects of introducing the cognitive modeling into the information and methodological support of the environmental assessment of complex objects are analyzed. The practical implementation of the proposed method is given using the forecasting of the state of Kharkov region as an example.